The role of hypoxic microenvironment in autoimmune diseases - Gong, Xun; Yang, Su-Yin; Wang, Zhen-Yu; Tang, Min (Frontiers in Immunology, 2024)
The hypoxic microenvironment, characterized by significantly reduced oxygen levels within tissues, has emerged as a critical factor in the pathogenesis and progression of various autoimmune diseases (AIDs). Central to this process is the hypoxia-inducible factor-1 (HIF-1), which orchestrates a wide array of cellular responses under low oxygen conditions. This review delves into the multifaceted roles of the hypoxic microenvironment in modulating immune cell function, particularly highlighting its impact on immune activation, metabolic reprogramming, and angiogenesis. Specific focus is given to the mechanisms by which hypoxia contributes to the development and exacerbation of diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), multiple sclerosis (MS), and dermatomyositis (DM). In these conditions, the hypoxic microenvironment not only disrupts immune tolerance but also enhances inflammatory responses and promotes tissue damage. The review also discusses emerging therapeutic strategies aimed at targeting the hypoxic pathways, including the application of HIF-1α inhibitors, mTOR inhibitors, and other modulators of the hypoxic response. By providing a comprehensive overview of the interplay between hypoxia and immune dysfunction in AIDs, this review offers new perspectives on the underlying mechanisms of these diseases and highlights potential avenues for therapeutic intervention.